Réforme de la formation en école de Masso-kinésithérapie : quels modes de réception par les formateurs ? - Thérèse Perez-Roux; Éric Maleyrot; Charlotte Pourcelot; Frédéric Rouvière; Bruno Boussagol (Éducation et Socialisation)
This contribution focuses on the trainers in the physiotherapists' initial training at the time of the 2015 studies reform. Using an online survey addressed to the French physiotherapy training institutes, the study seeks to understand the ways in which trainers appropriated this reform. The results highlight trainers' representations about the training activity and reform effects on them. They reveal an ambiguous process of universitarization / professionalisation as well as tensions and contradictions in the report to training activity. The training issues that emerge for the trainers themselves show the promising contributions by the sciences of education field.